2014
DOI: 10.3136/fstr.20.7
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds and Physicochemical Parameters of Grugru Palm (Acrocomia aculeata) from Brazil: Pulp and Powder

Abstract: As there is little study on grugru palm, the knowledge of the properties of the fruit pulp and powder is important in the fruit production recovering and in the enhancement of the processes of dehydration for better conservation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
6
0
4
Order By: Relevance
“…); vitamin A, 599.7 retinol equivalent/100 g (Oliveira et al . ); and minerals, i.e., potassium: 649.3 mg/100 g; calcium: 101.33 mg/100 g; and iron: 12.06 mg/100 g (Oliveira et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…); vitamin A, 599.7 retinol equivalent/100 g (Oliveira et al . ); and minerals, i.e., potassium: 649.3 mg/100 g; calcium: 101.33 mg/100 g; and iron: 12.06 mg/100 g (Oliveira et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…The literature does include several studies characterizing grugru palm pulp that found the following contents: protein, 3.0 to 1.5 g/100 g (Ramos et al 2008;Silva et al 2008;Oliveira et al 2013a); lipid, 18.2 to 13.8 g/100 g (Silva et al 2008;Oliveira et al 2013a); total sugars, 11.6 to 14.5 g/ 100 g; vitamin C, 28.0 to 135.5 mg/100 g (Sanjinez-Argandoña and Chuba 2011; Oliveira et al 2013a); vitamin A, 599.7 retinol equivalent/100 g (Oliveira et al 2014); and minerals, i.e., potassium: 649.3 mg/100 g; calcium: 101.33 mg/100 g; and iron: 12.06 mg/100 g (Oliveira et al 2013a). Thus, to use this raw material in the preparation of food products, it is necessary to describe the behavior of these nutrients from grugru palm pulp through the processes of drying and during the storage period.…”
Section: Introductionmentioning
confidence: 99%
“…O principal motivo da exploração antropogênica se deve ao seu meristema (palmito), que é utilizado na culinária brasileira (Galetti & Fernandez, 1998). Nos últimos anos, vários estudos foram realizados com E. edulis para mitigar esse cenário, principalmente em nível populacional e buscando entender os mecanismos envolvidos em sua germinação (de Barros Leite et al, 2012;Pizo et al, 2006), dispersão (da dos Santos et al, 2018), fenologia (Galleti, 1999;Tres et al, 2020) (Oliveira, Clemente, et al, 2014;Oliveira, Fisch, et al, 2014). Além de sua importância ecológica, E. edulis é uma das principais fontes de produtos florestais não madeireiros na MA, sendo amplamente utilizado como produto alimentício, ornamental e artesanal (Oliveira et al, 2017).…”
Section: Espécies Mais Estudadas E Tendência Temporal Nas Publicaçõesunclassified
“…(Pinto et al, 2018). This technique was also used in different studies using different carrier agents for the development of microencapsulated pequi oil, with a better protection as for its antioxidant activity compared to bulk oil (Oliveira et al, 2014). The anti-inflammatory activity of guavira microcapsules (Campomanesia adamantium) was tested in an animal model.…”
Section: Spray Dryingmentioning
confidence: 99%